PENGARUH TOTAL ASSET TURNOVER, RECEIVABLE TURNOVER, WORKING CAPITAL TURNOVER TERHADAP RETURN ON ASSET - Junaedi Junaedi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine: (1) The Effect of Total Asset Turnover on Return On Assets in Property and Real Estate Sub-Sector Companies, (2) The Effect of Receivable Turnover on Return On Assets in Property and Real Estate Sub-Sector Companies, (3) The Effect of Working Capital Turnover on Return On Assets in Property and Real Estate Sub-Sector Companies, (4) Effect of Total Asset Turnover, Inventory Turnover and Working Capital Turnover on Return On Assets in Property and Real Estate Sub-Sector Companies. The research method used in this study is the associative method. The object of the research is the Property and Real Estate sub-sector. The data sources used are from www.idx.co.id and the company's financial statements for 2016-2020. The data analysis techniques used are simple and multiple correlation tests, determination tests and simple and multiple regression tests. The results showed that total asset turnover, receivable turnover and working capital turnover on return on assets, had a strong and unidirectional (positive) effect. While the amount of the contribution given is 42.3% and the remaining 57.7%, where the rest is influenced by other factors not examined, one of which is inventory turnover. For this reason, the authors suggest that companies can pay attention to other factors that can affect the return on assets which will affect the net income on total assets used as the main goal of the company. Keywords: Total Asset Turnover, Receivable Turnover, Working Capital Turnover, Return on Asset